Linguistic nature of of antonyms in the works of Abai - Kalimova Ж.Ү. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article is devoted to the problem of antonymy as a linguistic phenomenon characteristic of all languages, with complex linguistic, stylistic and universal features and the scope of its use in language and fiction. The contradictory nature of antonyms as one of the original expressive means of the language is thoroughly described on the basis of the great Abai’s works. Antonyms are widely used to express the esthetic and stylistic nature of language in fiction.The article also deals with the way Abai carefully selects and uses words and expressions with opposite meanings in describing the social life of that time, the life of the Kazakh people, various types of behavior and actions of people. Different types of antonymy within the framework of antithesis, diathesis, acrotheses, alternatives, antitheses, antimetabols, oxymoron and their stylistic functions based on the poems and sayings of Abai are also described in detail in this article. Abai’s didactic words are considered to be an unprecedented work in the history of Kazakh literature. It is a valuable literary heritage, which reflects the deep thoughts and ideas of the poet. The article touches upon some Abai’s didactic words and draws the reader’s attention to the poet’s ability of using antonyms and antonymic phrases rationally and skillfully to describe the human life, to reveal the inner world of people and human psychology.